Clinical Relevance of the serum CTLA-4 in Cats with Mammary Carcinoma - Urbano, Ana Catarina (Sci Rep, 2020)
Cytotoxic T lymphocyte associated antigen 4 (CTLA-4) serves an important role in breast cancer progression, which has led to the development of novel immunotherapies aimed at blocking tumor immune evasion. Although feline mammary carcinoma is increasingly recognized as a valuable cancer model, no studies on CTLA-4 function had been conducted in this species. The serum CTLA-4, TNF-α and IL-6 levels of 57 female cats with mammary carcinoma were determined by ELISA, and immunohistochemistry was performed to evaluate CTLA-4 and FoxP3 expression in tumor cells and interstitial lymphocytes. The results obtained show that serum CTLA-4 levels are increased in cats with mammary carcinoma (P = 0.022), showing an association with a number of clinicopathological features: smaller tumor size, P < 0.001; absence of tumor necrosis, P < 0.001; non-basal status, P < 0.02 and HER-2-positive status. Additionally, a strong positive correlation was found between serum CTLA-4 levels and serum TNF-α (R = 0.88, P < 0.001) and IL-6 levels (R = 0.72, P < 0.001). Concerning the CTLA-4 and FoxP3 expression, although detected in both interstitial lymphocytes and tumor cells, a positive association was found only between interstitial CTLA-4 and FoxP3 expressions (R = 0.387, P = 0.01), which is negatively associated with the serum CTLA-4 levels (P = 0.03). These findings provide a preliminary step in the characterization of immune profiles in feline mammary carcinoma, uncovering a molecular rationale for targeted therapy with CTLA-4 pathway inhibitors. Finally, by strengthening the hypothesis of an immunomodulatory role for this regulator, we further validate the utility of spontaneous feline mammary carcinoma as a model for human breast cancer.